2016
DOI: 10.3991/ijac.v9i1.5748
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Organizational Culture and Knowledge Management in Tequila Companies from Mexico

Abstract: The purpose of this research is to determine the degree of association between organizational culture and knowledge management. Using a quantitative and cross-sectional design, the Pearson correlation coefficient was used to assess the relationship between variables, as well as a hierarchical multiple regression in order to measure the potential impact of organizational culture on knowledge management. To test some hypotheses, a sample of 39 tequila business organizations from the state of Jalisco was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Some authors have found a significant relationship between OC and KM (e.g., (Jassawalla and Sashittal, 2002;Lai, 2002;Glibsy and Holden, 2003;Lin and Lee, 2004;Lai and Lee, 2007;Palanisamy, 2007;Wang et al, 2011)). In Latin America, these variables have been studied from a theoretical (e.g., (Pérez and Coutín, 2005;Rojas, 2012)) and empirical perspective in Colombia (e.g., (Quiroga, 2007;López et al, 2011;Marulanda et al, 2016)) and Mexico (Nuñez et al, 2016).…”
Section: Organizational Culture (Oc) and Knowledge Management (Km)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have found a significant relationship between OC and KM (e.g., (Jassawalla and Sashittal, 2002;Lai, 2002;Glibsy and Holden, 2003;Lin and Lee, 2004;Lai and Lee, 2007;Palanisamy, 2007;Wang et al, 2011)). In Latin America, these variables have been studied from a theoretical (e.g., (Pérez and Coutín, 2005;Rojas, 2012)) and empirical perspective in Colombia (e.g., (Quiroga, 2007;López et al, 2011;Marulanda et al, 2016)) and Mexico (Nuñez et al, 2016).…”
Section: Organizational Culture (Oc) and Knowledge Management (Km)mentioning
confidence: 99%
“…Firstly, for the measurement of OC, an Organizational Culture Assessment Instrument (OCAI) was administered in its Spanish version, which is composed by 24 items, based on Cameron and Quinn (2006) To verify the reliability, which refers to the degree of consistency of an instrument, the Cronbach's α test was used (Hair et al, 2004). Both questionnaires were validated, where satisfactory results were reported in terms of reliability for the OC (Cameron and Freeman, 1991;Zammuto and Krakower, 1991;Choi et al, 2010;Strack, 2012) and KM (Mihi et al, 2011;Nuñez et al, 2016).…”
Section: Measurement Instrumentmentioning
confidence: 99%
“…OC has been studied in relation to individual-level outcomes (such as job satisfaction, organizational commitment, and turnover intention) (Salman et al , 2014), financial and social performance (Tanriverdi et al , 2016), safety and health (Živkovića and Ivanovab, 2016), and organizational structure (Csaszar, 2012). Barney’s well-known resource-based view recognizes OC as a key component to provide a competitive advantage to organizations (NuñezRamírez et al , 2016). In addition, it has a direct impact on the innovation strategy of organizations (Naranjo-Valencia et al , 2011).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Management research tends to focus on the nature and consequences of managerial actions whereas business research primarily focuses on the determinants of corporate performance (Easterby-Smith et al , 2012). In the complex and dynamic environment in which businesses function today, the culture of an organization is recognized as a crucial dimension that can either be an asset or a hindrance in shaping behavior in organizations and in achieving long-term organizational success (NuñezRamírez et al , 2016). As such, developing knowledge and understanding of organizational culture (OC) becomes increasingly important.…”
Section: Introductionmentioning
confidence: 99%
“…Leadership and organizational development dynamic environment businesses function today (NunezRamirez et al, 2016). Using the current lack of broader conceptual and methodological perspective in the organizational culture literature as a point of departure, Charlotte used an approach that has not been followed before, that is, using a number of sources with a primary focus on each of the following four identified types of basic knowledge orientations: Type I (culture theory research), Type II (culture science research), Type III (culture narrative research) and Type IV (culture development research).…”
mentioning
confidence: 99%